Further Results on Edge Product Cordial Labeling: Results on Edge Product Cordial Labeling - Aboshady, Mohamed; Elbarkouky, Reda; Roshdy, Eliwa; Seoud, Mohamed Abdel-Azim (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this paper, we present some properties of Edge Product Cordial graphs and make a survey on all graphs of order at most 6 to find out whether they are Edge Product Cordial or not. Finally, we study some families of graphs to be Edge Product Cordial or not: ????????2,???????? (????????) , ????????????????(????????), ????????????????⨀????????1, ????????????????⨀????????????????̅̅̅̅, ????????????????⨀????????????????̅̅̅̅, ???????????????? ∧ ???????????????? and the graph obtained from ???????????????? by attaching a pendant path ???????????????? to every vertex of ???????? .